2018
DOI: 10.1111/ajo.12807
|View full text |Cite
|
Sign up to set email alerts
|

Appendicectomy during pregnancy and the risk of preterm birth: A population data linkage study

Abstract: Appendicectomy during pregnancy is associated with increased risk of spontaneous and planned preterm birth, maternal and neonatal morbidity. Availability of resources to prevent or manage preterm labour should be considered when appendicectomy is performed at gestational ages of 20 weeks or more.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
41
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(43 citation statements)
references
References 25 publications
0
41
0
2
Order By: Relevance
“…As the operation in itself is unlikely to affect the risk of SGA immediately after surgery, we included a 14‐day lag‐time period, which likely explains why we found a less strong association with SGA. Ibiebele et al showed an equal risk of SGA in laparoscopy and laparotomy, confirming that it is acceptable to combine these procedures when studying the risk of SGA. As in most other studies, we found an increased risk of miscarriage following surgical procedures during pregnancy.…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…As the operation in itself is unlikely to affect the risk of SGA immediately after surgery, we included a 14‐day lag‐time period, which likely explains why we found a less strong association with SGA. Ibiebele et al showed an equal risk of SGA in laparoscopy and laparotomy, confirming that it is acceptable to combine these procedures when studying the risk of SGA. As in most other studies, we found an increased risk of miscarriage following surgical procedures during pregnancy.…”
Section: Discussionmentioning
confidence: 93%
“…Surgical procedures trigger both inflammatory and microbial responses, which may affect the fetus and timing of birth . The risk of adverse birth outcomes after surgery during pregnancy has been the topic of several studies . A systematic review of the literature until 2002 including 54 studies and 4473 women concluded that non‐obstetric surgery was probably not a risk factor for miscarriage .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations